Effects of pasteurization technologies and storage conditions on the flavor changes in acidified chili pepper - Xi Bao; Shiyao Zhang; Xueting Zhang; Yongli Jiang; Zhijia Liu; Xiaosong Hu; Junjie Yi (Current Research in Food Science, 2022)
In this study, the effects of thermal processing (TP), high pressure processing (HHP), and preservatives addition, i.e. sodium metabisulfite (SMS), on flavor changes in acidified chili peppers were compared. In addition, their changes during different storage periods (25, 37, and 42 °C for 30 days) were also investigated. The results indicate that TP clearly changed the flavor properties of acidified chili peppers compared to other processing, such as an increase in organic acid contents and titratable acid (TA) values but a decrease in pH value, free amino acid (FAA) concentrations, and some aromatic compound contents (e.g., esters and aldehydes). For SMS groups, more biter FAAs and higher alcohol concentrations were detected. Some terpenes (e.g., β-ocimene) significantly increased in samples after HPP (P < 0.05). In addition, storage conditions also clearly affected their flavor, particularly for high storage temperature. During storage, pH fast decreased but TA values and organic acids increased; FAAs firstly increased but followed decreased; esters and terpenes were the main compounds decreasing. Furthermore, some off-flavor related compounds were produced when samples were stored at high temperature, such as furans, aldehydes, and oxides. The outcome of this study could provide new insights into the effects of processing and storage conditions on flavor changes and guide production for the acidified chili pepper industry.